Research on Biological Behavior and The Synthesis of Various Heterocyclic Compounds - Rana Salah Noori Al-Saeagh; Maha Hameed Ismael; Ahmed Khudhair Al-Hamairy; Massar Aamer Merza; Rana Aqeel Ibrahim; Rusul Ahmed Mohammed (Central Asian Journal of Medical and Natural Science, 2025)
Heterocyclic compounds are found in almost 90% of new medications. Heterocyclic moiety is also present in several natural products, such as antibiotics like cephalosporins and penicillins, and alkaloids like morphine, vinblastine, and reserpine.Thioxanthone has been the source of three chemical compounds that have been produced as derivatives [S1, S2, and S3]. Every formatted chemical was tracked using melting point and FTIR spectra. This technique is suitable for industrial production and has a high target product productivity, gentle reaction conditions, straightforward purification methods, and high product purity. to further down the cost of production. The agar well diffusion method revealed that all three of the produced compounds had good antibacterial activity against the Gram-positive and Gram-negative bacteria under study, but S3 had the highest activity. To determine if the produced chemicals cause allergic reactions, a skin test for delayed hypersensitivity was conducted, and a test for animal mortality was conducted using killing mice.  In test animals, the substances elicit a strong cellular immunological response.